ANALISIS NARASI KAMPANYE DIGITAL DALAM MEMBENTUK EFIKASI POLITIK PEMUDA - Lubis, Putri Handayani; Rusfian, Effy Z; Puspita, Maria; Putri Handayani Lubis; Effy Z. Rusfian; Maria Puspita (JURNAL TAPIS, 2024)
Currently, campaigns are undergoing changes with the presence of social media, which is indicated by the development of political communication activities in election campaigns on social media. Sandiaga Uno uses social media to influence the political efficacy of young people, because in the interactive digital era, the production of political messages and images is very influential in mobilizing the votes of young voters. Campaign narratives are formed with narratives that appeal to young people. This study aims to explore the campaign narratives formed by Sandiaga Uno on Instagram social media and identify political efficacy narratives in shaping political efficacy attitudes in young people. This study is a qualitative study using thematic analysis methods. The results of this study found four narratives used by Sandiaga Uno in the digital campaign: the theme of social concern, youth participation, the richness of Indonesian cultural heritage, and leadership style. The theme of social concern, which was the most frequently posted, was successfully used by Sandiaga Uno to shape the political efficacy of young people.